Pengaruh Financial Distress, Good Corporate Governance, Dan Nilai Perusahaan Terhadap Tax Avoidance - Pratama, Nabilla Putri; Rustam, Akie Rusaktiva (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to empirically analyze the effect of financial distress, good corporate governance, and firm value of state-owned companies on tax avoidance with the proxy of CETR. Good corporate governance is represented by managerial ownership, institutional ownership, board of directors, board of independent commissioners, and audit committee as the main components of company organization. The research population includes state-owned mining companies listed on IDX between 2017 and 2020 from which the data of financial reports and annual reports are obtained. The samples of 17 companies are selected through the purposive sampling method, and analyzed by multiple linear regression utilizing SPSS 22. The results of this research proved that financial distress, managerial ownership, board of directors, board of independent commissioners, audit committee, and firm value did not affect tax avoidance, while institutional ownership had an effect on tax avoidance.